2006
DOI: 10.1093/bja/ael194
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation monitoring during vascular surgery: accuracy of the Hemochron ® low range activated clotting time (ACT-LR)

Abstract: Hemochron Jr Signature provides measurements of ACT-LR, which are accurate for monitoring heparin anticoagulation at anti-Xa activity below 0.8 u ml(-1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Correction for hematocrit altered the correlations; however the changes were slight most likely due to the exclusion of significantly anemic or polycythemic subjects from the population. The correlation of ACT-LR with anti-Xa levels in adult CCL decreases significantly when anti-Xa is greater than 1.0 IU/ml [24]. The anti-Xa activity levels resulting from UFH dosing in our CCL frequently exceeds 1.0 IU/ml (median 1.3) thus exceeding the intended range of the ACT-LR.…”
Section: Discussionmentioning
confidence: 76%
“…Correction for hematocrit altered the correlations; however the changes were slight most likely due to the exclusion of significantly anemic or polycythemic subjects from the population. The correlation of ACT-LR with anti-Xa levels in adult CCL decreases significantly when anti-Xa is greater than 1.0 IU/ml [24]. The anti-Xa activity levels resulting from UFH dosing in our CCL frequently exceeds 1.0 IU/ml (median 1.3) thus exceeding the intended range of the ACT-LR.…”
Section: Discussionmentioning
confidence: 76%
“…We showed that a strategy based on DOAC interruption that ensures undetectable DOAC concentration at the time of AF catheter ablation still resulted in a highly interindividual variability in UFH response, with a poor correlation between UFH dose and ACT levels and fewer than two‐thirds of the patients achieving ACT ≥300 seconds during the procedure. Indeed, ACT is accurate for monitoring UFH effects, as a strong and reproducible correlation between ACT and UFH anti‐Xa activity was repeatedly reported . However, several factors affect the anticoagulant response to fixed or weight‐adjusted UFH dose .…”
Section: Discussionmentioning
confidence: 99%
“…Racioppi et al have recently compared ACT-LR (Hemochron jr II Signature device) with APTT and have concluded that the poor correlation between ACT-LR and APTT does not support routine use of this device [19]. The same device was evaluated by Tremey et al in vascular surgery and was compared to anti-Xa activity [6]. They demonstrated the accuracy of the device, during vascular surgery, with the use of 50 UI·kg -1 UFH.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the ACT has been used for several decades in cardiac surgery as well as other procedures, and now in interventional neuroradiology [5][6][7]. Some controversies remain about the correlation between the different ACT monitoring devices and APTT [8].…”
Section: Introductionmentioning
confidence: 99%